Sinus Augmentation by Platelet-Rich Fibrin Alone: A Report of Two Cases with Histological Examinations. (3rd October 2016) - Aoki, Naofumi; Kanayama, Takeo; Maeda, Michinori; Horii, Koichiro; Miyamoto, Hironori; Wada, Keinoshin; Ojima, Yasutaka; Tsuchimochi, Tsukasa; Shibuya, Yasuyuki
Abstract : In sinus floor augmentation of an atrophic posterior maxilla, platelet-rich fibrin (PRF) has been used as a graft material. We herein report two cases with histological evaluations of PRF after the surgery. The first case was a 28-year-old female with an atrophic right posterior maxilla who was treated with sinus floor augmentation and simultaneous implant placement using PRF as the sole graft material in our hospital. Twenty-four months after surgery, the implant was unfortunately removed because of occlusal overloading by parafunctional habits. During implant replacement, a tissue sample was obtained from the site of augmentation with PRF and was evaluated histologically. The second case was a 58-year-old man with severe alveolar atrophy of the right maxilla who underwent lateral sinus augmentation using only PRF in a two-stage procedure in our hospital. Samples were obtained at the second-stage surgery and histological examinations were performed. As a result, new bone formation was confirmed histologically in both cases. Our findings show that the use of PRF as a graft material during sinus floor augmentation induces natural bone regeneration.